Some issues of legal regulation of labor relations with medical workers in Kazakhstan - Omarova, Э.Б.; Galiakbarova, Г.Г.; Abdilov, К.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The study of the legal status of a medical worker seems to be an important area of modern medical and legal research since it allows for the identification of gaps in the regulatory framework for the provision of medical services and the development of specific mechanisms for their elimination. It can be assumed that at present there are problems in the staffing of the healthcare sector due to the incompleteness of legislative norms regarding the rights and responsibilities of medical workers. The purpose of this article is to study the features of regulating the social and labor relations of medical workers. This article examines the features of the differentiation of medical workers' labor and determines the legal status of their labor. In addition, taking into account the latest changes in the current domestic legislation, an analysis of the current state of the legal status of a medical worker is carried out. It is determined that the regulation of labor relations of workers in the field of medicine is carried out by a set of various regulatory legal acts created on the basis of the principle of unity and differentiation of legal regulation of labor relations. Also, situations are determined when employees in this area are provided with additional payments and current measures of social support, and some features and problems arising in the process of their direct labor activity are indicated and disclosed. The special nature of their work is also indicated in connection with certain threats to the physical and emotional health of health workers, as well as special legal liability that arises in the event of a violation of their powers and duties.